Pengembangan Ekowisata Di Kawasan Hutan Provinsi Lampung - Idwin, Dedi; Herwanti, Susni (Universitas Pattimura, 2022)
The development of eco-tourism positively impacts managers, the surrounding community, and the government. Therefore, appropriate eco-tourism development is needed so that the benefits of eco-tourism can be optimal and have a broad impact. This study aims to analyze the development of eco-tourism in the forest area of ​​Lampung Province. Sampling was carried out intentionally on decision-makers in forest area management within the scope of the Lampung Provincial Forestry Service, including the Head of Service, Head of UPTD KPH, and Administrator Officers, as many as 22 respondents. The data were analyzed descriptively on the eco-tourism development strategy stated in the Domestik Minister Regulation Number 33 of 2009 concerning Guidelines for Ecotourism Development in the region, which includes planning, utilization, and control. The results showed that the development of eco-tourism in forest areas carried out by the Lampung Provincial Government from planning, utilization, and management was not optimal. The Lampung Provincial and Regency Governments need to form a coordination team as a forum for communication and coordination between eco-tourism actors so that the development carried out technically can run ideally. In addition, cooperation with investors also needs to be carried out to overcome budget constraints and build an integrated eco-tourism information and service center.